2008
DOI: 10.1007/bf03218579
|View full text |Cite
|
Sign up to set email alerts
|

The effect of salt and pH on the phase transition behaviors of pH and temperature-responsive poly(N,N-diethylacrylamide-co-methylacrylic acid)

Abstract: A series of pH and temperature-responsive (N,N-diethylacrylamide-co-methylacrylic acid) copolymers were synthesized by radical copolymerization and characterized by elemental analysis, Fourier-transform infrared (FT-IR), nuclear magnetic resonance (NMR)C and LLS. The effects of salt and pH on the phase transition behaviors of the copolymers were investigated by UV. With increasing NaCl concentration, significant salt effects on their phase transition behaviors were observed. UV spectroscopic studies showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The copolymerization of styrene and maleic anhydride has long been regarded as a classical example of an alternating radical copolymer system. [31][32][33][34] The alternating tendency in copolymerization has been explained by the participation of a 1:1 charge-transfer complex of styrene and maleic anhydride in the propagation step. 35,36 This is due to the fact that maleic anhydride does not homopolymerize under normal conditions and styrene forms a donor-acceptor complex with anhydride.…”
Section: Resultsmentioning
confidence: 99%
“…The copolymerization of styrene and maleic anhydride has long been regarded as a classical example of an alternating radical copolymer system. [31][32][33][34] The alternating tendency in copolymerization has been explained by the participation of a 1:1 charge-transfer complex of styrene and maleic anhydride in the propagation step. 35,36 This is due to the fact that maleic anhydride does not homopolymerize under normal conditions and styrene forms a donor-acceptor complex with anhydride.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the polymer containing 12%MAA showed no LCST in the range of 10–70 °C as a result of the very high hydrophilicity caused by the deprotonation of methacrylic acid at pH7 and the resulting strong formation of hydrogen bonds with water. In addition, the electrostatic repulsion among the ionized carboxylic acid groups could have stopped the polymer chains from aggregation …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, all the synthesized block copolymer micelles precipitated when the pH level was adjusted to 5. Although the PDEGMA homopolymer should not respond to pH changes, it was reported that high salt concentrations can decrease the strength of the hydrogen bonding between water molecules and hydrophilic chains . This contributes to a lower solubility and a higher tendency to self‐aggregate when the temperature increases.…”
Section: Resultsmentioning
confidence: 99%
“…The signal at approximately 34 ppm was attributed to the methylene carbon in NHC=OCH 2 groups [17]. Peaks between 9 -22 ppm can be attributed to CH 3 groups from side chains present in the polymer [20]. Signals at 19 and 27 ppm are most likely due to CH 2 -CH 2 type carbons.…”
Section: Nmr Analysismentioning
confidence: 99%